Achieving sustainability goals for urban coasts in the US Northeast: research needs and challenges. Issue 4 (3rd April 2017) - Close, Sarah L.; Montalto, Franco; Orton, Philip; Antoine, Adrienne; Peters, Danielle; Jones, Hunter; Parris, Adam; Blumberg, Alan
ABSTRACT: In the wake of Hurricane Sandy and other recent extreme events, urban coastal communities in the northeast region of the United States are beginning or stepping up efforts to integrate climate adaptation and resilience into long-term coastal planning. Natural and nature-based shoreline strategies have emerged as essential components of coastal resilience and are frequently cited by practitioners, scientists, and the public for the wide range of ecosystem services they can provide. However, there is limited quantitative information associating particular urban shoreline design strategies with specific levels of ecosystem service provision, and research on this issue is not always aligned with decision context and decision-maker needs. Engagement between the research community, local government officials and sustainability practitioners, and the non-profit and private sectors can help bridge these gaps. A workshop to bring together these groups discussed research gaps and challenges in integrating ecosystem services into urban sustainability planning in the urban northeast corridor. Many themes surfaced repeatedly throughout workshop deliberations, including the challenges associated with ecosystem service valuation, the transferability of research and case studies within and outside the region, and the opportunity for urban coastal areas to be a focal point for education and outreach efforts related to ecosystem services.